Rotation in Shawqi Bazie's Poetic Works - رحيم خريبط الساعدي; إسراء محمد العكراوي (آداب الكوفة, 2017)
Shawqi Bzei used rotation in his poems, trying to catch up with his fragmented fantasies, as if this rotation reflects the extent of the acceleration of the events around him with his helplessness in the face of them.